(untitled) - Soames, Roger W. (London, 2003)
This easy-to-read guide presents all the practical, essential information on joint movement that the clinician needs to know. Following a brief discussion of factors that may influence the range of movement, each chapter explores the relevant anatomy and possible movement of joints in the upper and lower limbs and vertebral column, as well as the temporomandibular joint. Highly illustrated with simple line diagrams, it outlines the principles of human joint movement, provides guidelines for clinical assessment, and presents the most effective, clinically based treatment options for dysfunction and limited range of motion.
Keywords: Motion,Joints,Chuyển động,Khớp; Range of motion,Measurement,Phạm vi của chuyển động,Đo lường